2018
DOI: 10.1038/s41419-018-0657-z
|View full text |Cite
|
Sign up to set email alerts
|

Gamma synuclein is a novel Twist1 target that promotes TGF-β-induced cancer cell migration and invasion

Abstract: Transforming growth factor β (TGF-β) is critical for embryonic development, adult tissue homeostasis, and tumor progression. TGF-β suppresses tumors at early stage, but promotes metastasis at later stage through oncogenes such as Twist1. Gamma-synuclein (SNCG) is overexpressed in a variety of invasive and metastatic cancer. Here, we show that TGF-β induces SNCG expression by Smad-Twist1 axis, thus promoting TGF-β- and Twist1-induced cancer cell migration and invasion. We identify multiple Twist1-binding sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 46 publications
1
52
0
Order By: Relevance
“…Emerging evidence shows that TGF-β/ALK/Smad signaling plays a role in carcinogenesis in many cancer types. 24 26 TGF-β signaling is reported to facilitate tumor growth and metastasis in advanced cancer, and blocking TGF-β/ALK/Smad signaling could suppress the process of epithelial-to-mesenchymal transition. 27 Geng et al 28 demonstrated that downregulation of PPM1A expression could promote invasion and epithelial-to-mesenchymal transition in bladder cancer by activating the TGF-β/Smad signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence shows that TGF-β/ALK/Smad signaling plays a role in carcinogenesis in many cancer types. 24 26 TGF-β signaling is reported to facilitate tumor growth and metastasis in advanced cancer, and blocking TGF-β/ALK/Smad signaling could suppress the process of epithelial-to-mesenchymal transition. 27 Geng et al 28 demonstrated that downregulation of PPM1A expression could promote invasion and epithelial-to-mesenchymal transition in bladder cancer by activating the TGF-β/Smad signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…4C). Given that Twist1 can be induced by TGF‐β [22], we additionally explore the interaction between endogenous Twist1 and TRIP in TGF‐β‐stimulated M619 cells via IP using antibodies specific for Twist1 or TRIP (Fig. 4D,E).…”
Section: Resultsmentioning
confidence: 99%
“…Through RNA-seq analysis, the DEGs related to TGF-β signalling were identified in response to combination treatment of vactosertib with nal-IRI/5-FU/LV. For example, BCL9L and SNCG are involved in TGF-β-induced EMT, migration, invasion, and metastasis 32,33 . The expression of BCL9L is up-regulated in pancreatic cancer 34 , and knockdown of BCL9L diminishes TGF-β-induced EMT responses in pancreatic cancer cells and inhibits liver metastasis in vivo 32 .…”
Section: Ectopic Expression Of Ccdc80 In Pancreatic Cancer Cells Decrmentioning
confidence: 99%
“…The expression of SNCG is up-regulated in breast, colon, and pancreatic cancers [35][36][37] . SNCG is involved in perineural invasion associated with local recurrence and dismal prognosis in relation with TGF-β or Twist in pancreatic cancer 33 . In this study, we found that combination treatment of vactosertib with nal-IRI/5-FU/LV significantly reduced SNCG and BCL9L expression.…”
Section: Ectopic Expression Of Ccdc80 In Pancreatic Cancer Cells Decrmentioning
confidence: 99%